Pengaruh Pemberian Sediaan Creambath Ekstrak Daun Kembang Sepatu (Hibiscus Rosa-Sinensis) pada Pertumbuhan Rambut Kelinci (New Zealand) - Widyastuti, Lita; Ningsih, Dwi; Aisiyah, Siti (Jurnal Farmasi (Journal of Pharmacy), 2019)
Hibiscus rosa-sinensis is contains flavonoids, saponins and polyphenols that play a role in accelerating the growth of hair.This research aims to know the influence of the variation of concentration of ethanol extracts of hibiscus leaves in preparation creambath against rabbit hair growth. Of ethanol extracts of hibiscus leaves are obtained with the method remaseration using ethanol 70%. Creambath preparation made in 4 formula with the concentration of the extract of hibiscus in 10%, 15%, 20% and a negative control. Applied to the backs of rabbits that had been shaved and then given the preparations-2 times a day for 15 days. To test the activity of rabbit hair growth by measuring the length of the hair and rabbit hair, weight and physical test performed which include odor, color, pH, spread power, power protection, the ability to say, type, viscosity and stability of creams, creambath. Physical quality test data, weight, and hair is analyzed with the Saphiro-Wilk, then using ANOVA and Post Hoc Tests. The results showed that preparations creambath hibiscus leaves ethanol extract with a concentration of 10%, 15%, and 20% have good physical stability. The higher the concentration of the extract in preparations creambath hair growth activity differences produce rabbits. The results views of the parameter weights and lengths of hair, but not yet as effective as comparison control formula that delivers results-effective against the growth of rabbit hair creambath is with a concentration of 20%.